Cationic phosphorus dendrimers and therapy for Alzheimer's disease. (2nd June 2015) - Wasiak, Tomasz; Marcinkowska, Monika; Pieszynski, Ireneusz; Zablocka, Maria; Caminade, Anne-Marie; Majoral, Jean-Pierre; Klajnert-Maculewicz, Barbara
<x xml:space="preserve">Abstract</x> Cationic phosphorus dendrimers show a weak antioxidant potential, reduce the level of TNF-alpha and mimic partial noncompetitive inhibitors of AChE.